2016
DOI: 10.1200/jco.2016.67.9613
|View full text |Cite
|
Sign up to set email alerts
|

HIV Infection and Survival Among Women With Cervical Cancer

Abstract: Purpose Cervical cancer is the leading cause of cancer death among the 20 million women with HIV worldwide. We sought to determine whether HIV infection affected survival in women with invasive cervical cancer. Patients and Methods We enrolled sequential patients with cervical cancer in Botswana from 2010 to 2015. Standard treatment included external beam radiation and brachytherapy with concurrent cisplatin chemotherapy. The effect of HIV on survival was estimated by using an inverse probability weighted marg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
156
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 143 publications
(184 citation statements)
references
References 47 publications
12
156
4
1
Order By: Relevance
“…Those studies estimated a 1.7- to 2.0-fold increased risk of death associated with HIV infection. There are, however, several key differences between our study and those prior studies that may explain our discordant findings (16, 17, 28). In contrast to our study in which only women being treated with curative CRT were included, the 3 previous studies included women being treated with both palliative and curative intent.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Those studies estimated a 1.7- to 2.0-fold increased risk of death associated with HIV infection. There are, however, several key differences between our study and those prior studies that may explain our discordant findings (16, 17, 28). In contrast to our study in which only women being treated with curative CRT were included, the 3 previous studies included women being treated with both palliative and curative intent.…”
Section: Discussioncontrasting
confidence: 99%
“…However, our findings are discordant with results from a previous study in Botswana by Dryden-Peterson et al (17) (2016), from an analysis of administrative datasets of women in the United States with cervical cancer by Coghill et al (16) (2015), and from a retrospective study in Brazil by Ferreira et al (28) (2017). Those studies estimated a 1.7- to 2.0-fold increased risk of death associated with HIV infection.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Positive HIV status was associated with an HR of 3.7 (CI 95% 1.3-10.2; p=0.009) of residual tumor. -Peterson et al (2016) reported that 3-year survival for HIV positive patients was only 35% in Botswana, a rate lower to our 3-year OS rate, which could exceed 50%. In a non-VIH population, Han, Milosevic, Fyles, Pintilie & Viswanathan, (2013) showed that the 5-year OS rate was decreased in absence of brachytherapy (46% versus 58%), a rate similar to our 5-year OS.…”
Section: Survivalmentioning
confidence: 48%